2011
DOI: 10.1007/s00125-010-2042-z
|View full text |Cite
|
Sign up to set email alerts
|

Leucocytes are a major source of circulating nicotinamide phosphoribosyltransferase (NAMPT)/pre-B cell colony (PBEF)/visfatin linking obesity and inflammation in humans

Abstract: Aims/hypothesisNicotinamide phosphoribosyltransferase (NAMPT) is a multifunctional protein potentially involved in obesity and glucose metabolism. We systematically studied the association between circulating NAMPT, obesity, interventions and glucose metabolism and investigated potential underlying inflammatory mechanisms.MethodsFasting morning NAMPT serum levels were measured in cohorts of lean vs obese children, cohorts of intervention by lifestyle, exercise and bariatric surgery, and during an OGTT. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
124
4
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(149 citation statements)
references
References 49 publications
5
124
4
11
Order By: Relevance
“…Weight loss after exercise program causes reduced serum levels of visfatin (15) and this reinforces the theory that reduced visfatin is associated with improved insulin sensitivity (3). Much evidence show that physical activity is associated with reduced cardiovascular diseases which cause mortality in the general population, and in patients with type 2 diabetes mellitus.…”
Section: Introductionsupporting
confidence: 69%
“…Weight loss after exercise program causes reduced serum levels of visfatin (15) and this reinforces the theory that reduced visfatin is associated with improved insulin sensitivity (3). Much evidence show that physical activity is associated with reduced cardiovascular diseases which cause mortality in the general population, and in patients with type 2 diabetes mellitus.…”
Section: Introductionsupporting
confidence: 69%
“…Its role in metabolic processes is still controversial, but it has been reported that the properties of visfatin are similar to insulin. It has been suggested that the levels of visfatin are higher in obese [44,45] and in OA patients [46]. In an experimental study, it has been found that visfatin level could be down-regulated by the overexpression of miR34a, which binds directly to the 3′UTR of visfatin mRNA.…”
Section: Visfatinmentioning
confidence: 99%
“…Instead, it can be secreted into the extracellular space or into the blood via a non-classical secretory mechanism 13 by a number of cell types, such as adipocytes, hepatocytes, macrophages, and leukocytes. [14][15][16] Whether neuronal cells also secrete eNAMPT and its potential function in the CNS remain unknown. In the present study, we observed that transgenic mice overexpressing NAMPT in a neuron-specific manner were highly resistant to focal cerebral ischemic brain damage.…”
Section: Introductionmentioning
confidence: 99%